2009
DOI: 10.2202/1542-6580.1942
|View full text |Cite
|
Sign up to set email alerts
|

Electrocoagulation of Textile Effluent: RSM and ANN Modeling

Abstract: This investigation attempts to study electrocoagulation of Acid Blue 113 textile effluent in a batch electrochemical reactor covering wide range in the operating conditions. Experiments were designed using statistical tool of Response Surface Method (RSM) to analyze the combined effect of operating parameters on the efficiency of electro coagulation process. The level of importance of the experimental parameters on the percentage COD removal has been determined by using analysis of variance (ANOVA). Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The relationship between the response ( y ) and the independent variables were expressed in Equation 6 (Murugan et al., 2009):y=fx1,x2,x3.xk+ε,where x 1 , x 2 , x 3 , …, x k are the independent variables, ε is the error term, while k refers to the number of independent variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the response ( y ) and the independent variables were expressed in Equation 6 (Murugan et al., 2009):y=fx1,x2,x3.xk+ε,where x 1 , x 2 , x 3 , …, x k are the independent variables, ε is the error term, while k refers to the number of independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between the response (y) and the independent variables were expressed in Equation 6 (Murugan et al, 2009):…”
Section: Rsm Modelingmentioning
confidence: 99%
“…Since then, various carbon‐coating methods have been published by using different carbon sources, most of which are based on the decomposition of organic precursors, such as sugars,2 polymers,3 or glycols4 in inert or reducing atmosphere. When such carbon‐coating methods are applied to classical cathodic materials, such as highly oxidized transition metal oxides, they often reduce the compound even to the elemental metal.…”
Section: Summary Of Known Crystal Structures Of Lixv2o510amentioning
confidence: 99%
“…Appendix Table 5 provides a summary table considering the parameters and the dye(s) treated. Upon further assessments, it is observed that only two authors considered varying dyes (albeit they are from the same classification) (Körbahti 2007;Murugan et al 2009), while only one employed combined electrocoagulation/chemical coagulation using only one coagulant (powdered activated carbon) (Taheri et al 2013). An investigation of several textile dyes is important because the physical and chemical nature of conventional textile dye wastewater can be very complex.…”
Section: Introductionmentioning
confidence: 99%